Neurochemical and Behavioral Profiling in Male and Female Rats of the Psychedelic Agent 25I-NBOMe - Miliano, Cristina; Marti, Matteo; Pintori, Nicholas; Castelli, Maria Paola; Tirri, Micaela; Arfè, Raffaella; De Luca, Maria Antonietta (Frontiers in Pharmacology, 2019)
25I-NBOMe, commonly called “N-Bomb”, is a synthetic phenetylamine with psychedelic and entactogenic effects; it was available on the Internet both as a legal alternative to LSD and as a surrogate of MDMA, but now it has been scheduled among controlled substances. 25I-NBOMe acts as full agonist on 5-HT2A receptors. Users are often unaware of ingesting fake LSD, and several cases of intoxication and fatalities have been reported. Overdoses of “N-Bomb” can cause tachycardia, hypertension, seizures, and agitation. The rewarding properties and behavioral effects of this compound have not been widely investigated yet in both sexes. Therefore, by in vivo microdialysis we evaluated the effects of 25I-NBOMe on DA and 5-HT transmissions in NAc shell and core, and mPFC of male and female rats. Moreover, we investigated the effect of 25I-NBOMe on sensorimotor modifications as well as body temperature, nociception and startle/prepulse inhibition (PPI). We showed that administration of 25I-NBOMe affects DA transmission in the NAc shell in both sexes, although showing different patterns; moreover, this compound causes impaired visual responses in both sexes, whereas core temperature is heavily affected in females, and the highest dose tested exerts an analgesic effect prominent in male rats. Indeed, this drug is able to impair the startle amplitude with the same extent in both sexes and inhibits the PPI in male and female rats. Our study fills the gap of knowledge on the behavioral effects of 25I-NBOMe, and the risks associated with its ingestion; it focuses the attention on sex differences that might be useful to understand the trend of consumption, as well as to recognize and treat intoxication and overdose symptoms.